2001
DOI: 10.1001/archpedi.155.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reducing Children's Television and Video Game Use on Aggressive Behavior

Abstract: An intervention to reduce television, videotape, and video game use decreases aggressive behavior in elementary schoolchildren. These findings support the causal influences of these media on aggression and the potential benefits of reducing children's media use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
1
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 25 publications
3
113
1
10
Order By: Relevance
“…Other research (Rentfrow & Gosling, 2003) also revealed that people consider music an important aspect of their lives, which is at least as important as most other leisure activities. This has led to the suggestion that media exposure could be an important determinant of pro- (Mares & Woodard, 2005) and antisocial behavior (Robinson, Wilde, Navracruz, Haydel, & Varady, 2001). However, whereas negative effects of exposure to media with violent content on aggressive behavior are well-documented, research on the effects of media with prosocial content on prosocial tendencies has been relatively sparse.…”
mentioning
confidence: 99%
“…Other research (Rentfrow & Gosling, 2003) also revealed that people consider music an important aspect of their lives, which is at least as important as most other leisure activities. This has led to the suggestion that media exposure could be an important determinant of pro- (Mares & Woodard, 2005) and antisocial behavior (Robinson, Wilde, Navracruz, Haydel, & Varady, 2001). However, whereas negative effects of exposure to media with violent content on aggressive behavior are well-documented, research on the effects of media with prosocial content on prosocial tendencies has been relatively sparse.…”
mentioning
confidence: 99%
“…This growing interest in playing video games has raised concerns about the consequences of video game play. In fact, playing video games with violent content may lead to criminal actions (Anderson & Dill, 2000) and physical violence (Gentile et al, 2004), whereas reducing children's exposure to media violence reduces aggressive tendencies (Robinson, Wilde, Navracruz, Haydel, & Varady, 2001). Thus, there is clear evidence that media exposure can be harmful to social relations.…”
mentioning
confidence: 99%
“…48 In addition, studies have shown adequate correlation between the results of parent reports of child behavior and independent observations. 49,50 Finally, the study was conducted in a single geographic area and may not be generalizable to other parts of the country.…”
Section: Discussionmentioning
confidence: 99%